Detrimental Effects of Restricted Cage Size on Reproductive Performance, Exploration Ability, and Anxiety but Not Working Memory of Kunming Mice - An, Wenzhen; Zhang, Ying; Zhou, Aibao; Hu, Yuzheng (Frontiers in Behavioral Neuroscience, 2021)
A suboptimal housing environment such as small cage size can adversely influence many aspects of the biology of laboratory animals including their response in behavioral tests. However, the effect of cage size on the mental and physical conditions of Kunming mice, that have been widely used to develop models of depression, anxiety, and many other diseases in China, are still far from clear. The purpose of this study was to investigate the effects of cage size on reproductive ability, exploratory behavior, anxiety and working memory of Kunming mice. Two cage sizes were used, including a standard cage (20×30×25 cm3) and a restricted cage(10×20×25 cm3) were used. The results revealed that, compared with mice in the standard cages, mice in the restricted cages showed I) a decreased delivery rate of dams (P＜0.05) and a lower survival rate of offspring (P＜0.05), specifically in females (P＜0.05); II) a decreased exploratory behavior (P＜0.01) and increased anxiety level (P＜0.01); and III) higher working memory in the T-maze test (P＜0.05). These results indicated that a restricted cage size has detrimental effects on the reproductive ability and anxiety level, but its effect on cognitive ability is complex and warrants further study. In short, these results provide empirical evidence for better practices in caring for Kunming mice, with some cautions about the effects of cage size on behavioral tests.